Animal minds, animal souls, animal rights - Parker, James V. (University Press of America, 2010)
A philosophical and theological exploration of animal consciousness and animal rights. The author lays down a foundation for a contemporary ethic in which people exercise intelligent stewardship and ensure the compassionate treatment of animals.